Marathon running leads to partial exhaustion of ROS-generating capacity in leukocytes - Nielsen, H. G.; Hagberg, I. A.; Lyberg, T. (Medicine & Science in Sports & Exercise, 2004)
PURPOSE: The aim of the present study was to investigate the changes occurring in leukocyte levels of reactive oxygen species (ROS) and total blood plasma antioxidant capacity (TAS) as a result of a marathon/half-marathon race.